Single-incision versus multi-port laparoscopic ileocolic resections for Crohn's disease: Systematic review and meta-analysis - Pratik Bhattacharya; Mohammad Iqbal Hussain; Shafquat Zaman; Elizabeth Peterknecht; Yousaf Tanveer; Ali Yasen Mohamedahmed; Akinfemi Akingboye; Rajeev Peravali (Journal of Minimal Access Surgery, 2023)
Introduction: The aim of this systematic review and meta-analysis is to compare the outcomes of single-incision laparoscopic surgery (SILS) versus multi-port laparoscopy for ileocolic resection in patients with Crohn's disease (CD). Patients and Methods: A systematic search of multiple electronic databases was conducted. The peri- and post-operative outcomes were evaluated between Crohn's patients undergoing SILS versus multi-port laparoscopy for ileocolic resection. The primary outcomes included operative time, anastomotic leak rate, post-operative wound infections and length of hospital stay. Analysed secondary outcomes were conversion rates, ileus occurrence, intra-abdominal abscess formation, return to theatre and re-admissions. Revman 5.3 was used to perform the statistical analysis. Results: Five observational studies with 521 patients (SILS: 211; multi-port: 310) were included in the data synthesis. Patients undergoing SILS had a reduced total operative time compared to multi-port laparoscopy (mean difference [MD]: −16.14, 95% confidence interval: [CI] −27.23 − 5.05, P = 0.004). Post-operative hospital stay was also found to be significantly less in the SILS group (MD: −0.57, 95% CI: −0.73–−0.42, P < 0.0001). No significant difference was seen in the anastomotic leak rate (MD: −16.14, 95% CI: 0.18–1.71, P = 0.004) or post-operative wound infections (odds ratio: 0.78, 95% CI: 0.24 − 2.47, P = 0.67) between the two groups. Moreover, all the measured secondary outcomes were comparable. Conclusion: SILS seems to be a feasible alternative to multi-port laparoscopic surgery for ileocolic resection in patients with CD. Improved outcomes in terms of total operative time and length of hospital stay were observed in patients undergoing SILS surgery. Adopting this procedure into routine clinical practice constitutes the next step in the development of minimally invasive surgery.